A stapled chromogranin A-derived peptide is a potent dual ligand for integrins αvβ6 and αvβ8. Issue 98 (22nd November 2019) - Nardelli, Francesca; Ghitti, Michela; Quilici, Giacomo; Gori, Alessandro; Luo, Qingqiong; Berardi, Andrea; Sacchi, Angelina; Monieri, Matteo; Bergamaschi, Greta; Bermel, Wolfgang; Chen, Fuxiang; Corti, Angelo; et al.
Abstract : Combining 2D STD-NMR, computation, biochemical assays and click-chemistry, we have identified a chromogranin-A derived compound (5 ) that has high affinity and bi-selectivity for αvβ6 and αvβ8 integrins and is stable in microsomal preparations. Abstract : Combining 2D STD-NMR, computation, biochemical assays and click-chemistry, we have identified a chromogranin-A derived compound (5 ) that has high affinity and bi-selectivity for αvβ6 and αvβ8 integrins and is stable in microsomal preparations. 5 is suitable for nanoparticle functionalization and delivery to cancer cells, holding promise for diagnostic and/or therapeutic applications.